2013
DOI: 10.1007/s00429-013-0552-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific gray matter volume differences in females with developmental dyslexia

Abstract: Developmental dyslexia, characterized by unexpected reading difficulty, is associated with anomalous brain anatomy and function. Previous structural neuroimaging studies have converged in reports of less gray matter volume (GMV) in dyslexics within left hemisphere regions known to subserve language. Due to the higher prevalence of dyslexia in males, these studies are heavily weighted towards males, raising the question whether studies of dyslexia in females only and using the same techniques, would generate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 117 publications
3
54
0
Order By: Relevance
“…The second finding is more difficult to explain in the context of reports of increased prevalence of DLD among boys compared to girls (Shriberg, Tomblin, & McSweeny, 1999; Tomblin et al, 1997). However, it is possible that it reflects the sex specificity of the etiological mechanisms underlying the manifestation of DLD, as has, for example, been suggested for other communication and learning disorders (e.g., Evans, Flowers, Napoliello, & Eden, 2014; Suresh et al, 2006). …”
Section: Discussionmentioning
confidence: 97%
“…The second finding is more difficult to explain in the context of reports of increased prevalence of DLD among boys compared to girls (Shriberg, Tomblin, & McSweeny, 1999; Tomblin et al, 1997). However, it is possible that it reflects the sex specificity of the etiological mechanisms underlying the manifestation of DLD, as has, for example, been suggested for other communication and learning disorders (e.g., Evans, Flowers, Napoliello, & Eden, 2014; Suresh et al, 2006). …”
Section: Discussionmentioning
confidence: 97%
“…The subjects were a subset of a group of children participating in a larger study on reading, reading disability, and reading development (Evans et al, 2013; Krafnick et al, 2014; Krafnick et al, 2011; Olulade et al, 2013a; Olulade et al, 2013b). Subjects with developmental dyslexia had a documented history of their reading disability, and most attended a school that specializes in the teaching of children with learning disabilities.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, all 7 LD-identified students were male and in the exclusive top left and inverted bimanual groups. While suggestive, it is still unclear whether or not a gender difference related to this particular bimanual rotation laterality exists; new research identifying female dyslexia may contribute to this finding (Evans et al, 2013).…”
Section: Discussionmentioning
confidence: 99%